Pharmacogenetics in electroconvulsive therapy and adjunctive medications. (June 2015) - Mirzakhani, Hooman; van Noorden, Martijn S; Swen, Jesse; Nozari, Ala; Guchelaar, Henk-Jan
Electroconvulsive therapy (ECT) has shown apparent efficacy in treatment of patients with depression and other mental illnesses who do not respond to psychotropic medications or need urgent control of their symptoms. Pharmacogenetics contributes to an individual's sensitivity and response to a variety of drugs. Clinical insights into pharmacogenetics of ECT and adjunctive medications not only improves its safety and efficacy in the indicated patients, but can also lead to the identification of novel treatments in psychiatric disorders through understanding of potential molecular and biological mechanisms involved. In this review, we explore the indications of pharmacogenetics role in safety and efficacy of ECT and present the evidence for its role in patients with psychiatric disorders undergoing ECT.